The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/cells9040906
|View full text |Cite
|
Sign up to set email alerts
|

A Commercial Probiotic Induces Tolerogenic and Reduces Pathogenic Responses in Experimental Autoimmune Encephalomyelitis

Abstract: Previous studies in experimental autoimmune encephalomyelitis (EAE) models have shown that some probiotic bacteria beneficially impact the development of this experimental disease. Here, we tested the therapeutic effect of two commercial multispecies probiotics-Lactibiane iki and Vivomixx-on the clinical outcome of established EAE. Lactibiane iki improves EAE clinical outcome in a dose-dependent manner and decreases central nervous system (CNS) demyelination and inflammation. This clinical improvement is relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 68 publications
1
41
0
Order By: Relevance
“…For this reason, preclinical studies are important. Heat-killed L. reuteri GMNL- 263 was found to be effective in preventing cardiac damage in a model of systemic lupus erythematosus ( 223 ); in a second study, a commercially prepared probiotic, Lactibiane Iki , controlled active EAE by promoting tolerogenic DC ( 224 ); and the combined administration of two Bifidobacteria and Lactobacilli probiotic strains prevented experimental myasthenia gravis ( 225 ). Preclinical studies of probiotics are in progress but to date no randomized controlled trials of probiotics in patients with uveitis have been reported.…”
Section: What Does the Gut–central Nervous System Axis Imply For Thermentioning
confidence: 99%
“…For this reason, preclinical studies are important. Heat-killed L. reuteri GMNL- 263 was found to be effective in preventing cardiac damage in a model of systemic lupus erythematosus ( 223 ); in a second study, a commercially prepared probiotic, Lactibiane Iki , controlled active EAE by promoting tolerogenic DC ( 224 ); and the combined administration of two Bifidobacteria and Lactobacilli probiotic strains prevented experimental myasthenia gravis ( 225 ). Preclinical studies of probiotics are in progress but to date no randomized controlled trials of probiotics in patients with uveitis have been reported.…”
Section: What Does the Gut–central Nervous System Axis Imply For Thermentioning
confidence: 99%
“…Yet, Prevotella comprise a large number of species, a fact that probably explains these contradictory data. In contrast, elevated salt intake was associated with a reduction of Lactobacillus [50,61], a genus that was beneficially linked to effects in colitis [64], salt-induced hypertension [50], and neuroinflammation [49][50][51]. During neuroinflammation, the high-salt-induced depletion of Lactobacillus was paralleled by the induction of Th17 cells in the gut and spleen, coinciding with deteriorating EAE symptoms [50].…”
Section: Modulations Of the Gut Microbiota And Its Metabolites By Higmentioning
confidence: 99%
“…Moreover, tryptophan metabolites may modulate T-cell subsets by either promoting Th1 and Th17 differentiation or by the induction of Treg cells (reviewed in [47]). Interestingly, tryptophan metabolites can be produced by different strains from the bacteria genera Lactobacillus [48], and Lactobacilli were recently shown to ameliorate EAE by reducing Th1 and Th17 cells [49][50][51]. In addition, neurotransmitters such as gamma amino butyric acid, serotonin, or norepinephrine can be produced by gut microorganisms [52][53][54] and may have a potential role in MS pathogenesis [55].…”
Section: Potential Mechanism Of Microbial Changes Obtained In Animal mentioning
confidence: 99%
“…However, treatment with a mixture containing all three strains successfully reversed established EAE and was associated with systemic IL-10 release and induction of Tregs in lymph nodes, periphery, and CNS [ 62 ]. A more recent study compared the protective effects of two commercially available probiotic mixes against EAE induced in C57BL/6 mice: Lactibiane Iki, composed of Bifidobacterium lactis LA 304, Lactobacillus acidophilus LA 201, and Lactobacillus salivarius LA 302; and Vivomix, composed of Lactobacilli, Bifidobacteria, and Streptococcus thermophilus [ 152 ]. Both probiotics reduced the extent of demyelination and T cell levels in the spinal cords of EAE mice, modified the intestinal microbiota, and affected the levels of antigen presenting cell (APC) immune cells.…”
Section: Interventions Of the Intestinal Microbiota As A Treatmentmentioning
confidence: 99%
“…Similarly, treatment with Lactibiane Iki increased the populations of Tregs in the periphery while reducing the percentages of plasma cells in circulation. Lactibiane Iki furthermore was able to reduce the severity of EAE [ 152 ]. As we continue to learn how probiotics intersect with the immune system, targeted probiotic treatment will allow us to modify the intestinal microbiota to decrease inflammation, promote immune health, and to prevent or ameliorate symptoms associated with MS and other inflammatory diseases.…”
Section: Interventions Of the Intestinal Microbiota As A Treatmentmentioning
confidence: 99%